АРХІТЕКТУРА МЕХАНІЗМІВ ОБРОБКИ ДАНИХ ТА СИНХРОНІЗАЦІЯ МОДУЛІВ У ВИСОКОНАВАНТАЖЕНИХ СИСТЕМАХ SMART CITY (World Science, 2018)
The study is aimed to determine the main problem during developing and maintaining services of high load Smart City system and propose solutions for achieving eventual consistency between services. The main problem with the services and databases is a significant amount of requests which is produced by millions of devices and how to process and store it quite fast. Low latency, high scalability and failure resistance should be the main characteristic of the system. That is why choosing a database, a right strategy for database replicas, service synchronization and its monitoring are basic problems which must be solved first. There are several architecture and database types which are already used in more simple systems. Key aspect needs to be resolved – how to synchronize data between multiple services in Smart City system. To solve the problems we need to redevelop already existing technology which is used for more simple problems, join them and apply on new solution.